The impact of digitalization on the financial sector - Póta, Cserne Panka; Becsky-Nagy, Patrícia (Competitio, 2022)
Present-day consumer society increasingly satisfies its needs through digital channels, and financial products and services are no exceptions. The 4th industrial revolution is not only about the penetration of technology, but also the paradigm shift of business processes. The traditional members of the financial sector must adapt to the digitalized world to keep their positions in the market. The penetration of BigTech and FinTech companies influenced the expectations of consumers: customer experience became the main criteria of their decisions. In order to simplify and accelerate processes, banks use the methods of digitalization, and automatize the system to increase client satisfaction. In this article, we will introduce the three bank types based primarily on the usage of innovative technology, the extension and depth of the cooperation with FinTech companies, and the status of a bank’s internal digital transformation. Also, we will introduce the current status of the banking sector evidenced by our SWOT-analysis and mention some of the existing payment solutions. JEL Classification: G21, G23